2020
DOI: 10.1098/rspa.2019.0800
|View full text |Cite
|
Sign up to set email alerts
|

Learning partial differential equations for biological transport models from noisy spatio-temporal data

Abstract: We investigate methods for learning partial differential equation (PDE) models from spatio-temporal data under biologically realistic levels and forms of noise. Recent progress in learning PDEs from data have used sparse regression to select candidate terms from a denoised set of data, including approximated partial derivatives. We analyse the performance in using previous methods to denoise data for the task of discovering the governing system of PDEs. We also develop a novel methodology that uses art… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 40 publications
(93 reference statements)
0
76
0
Order By: Relevance
“…Note that this weighting factor makes BINNs sensitive to the random choice of training/validation split, since some data points in the initial condition may be more informative than others for equation learning and ultimate model generalizability. This observation was also noted in a recent equation learning study in which the random split of training and validation sets was found to influence the structure of the learned equation [26]. Adopting a strategy similar to this previous study, BINNs were trained 20 times for each data set (using different random training/validation splits).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Note that this weighting factor makes BINNs sensitive to the random choice of training/validation split, since some data points in the initial condition may be more informative than others for equation learning and ultimate model generalizability. This observation was also noted in a recent equation learning study in which the random split of training and validation sets was found to influence the structure of the learned equation [26]. Adopting a strategy similar to this previous study, BINNs were trained 20 times for each data set (using different random training/validation splits).…”
mentioning
confidence: 55%
“…is used with proportionality constant γ = 0.2. Note that γ was tuned numerically following the methodology suggested in [26] (see Methods Section for more details). The next term L PDE ensures u MLP satisfies the solution of the governing PDE.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…First, a de-noise technique can be implemented prior to the hybrid model development so that the noise in the measurements will become less influential. In the literature, various methods such as finite difference with polynomial spline [67], spectral transformation [68], sparse Bayesian regression [69], and neural networks [70] have been proposed. Second, alternative ANN training mechanisms can be implemented to improve the performance of an ANN.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Use ANN's to discover the PDE form of biological transport equations from noisy data. [21] C. MLaroundHPC: Learning Model Details -ML for Data Assimilation (predictor-corrector approach) Data assimilation involves continuous integration of time dependent simulations with observations to correct the model with a suitable combined data plus simulation model. This is for example common practice in weather prediction field.…”
Section: ) Particle Dynamics-mlautotuninghpc -Learning Model Setups mentioning
confidence: 99%